"THE RESEARCH OF PARALINGUISTIC ELEMENTS IN DIPLOMATIC DISCOURSE" (Scientific journal of the Fergana State University, 2025)
Diplomatic discourse is a set of elements, which demonstrates a unique harmony expressed through verbal and paralinguistic factors, essential for success in international relations. While communication is primarily conveyed through language, paralinguistic concepts such as intonation, speech tempo, volume, rhythm and body movements also contribute to the effectiveness of diplomatic discourse. In this article, the author explores how paralinguistic factors in diplomatic speech affect international unity, the success of the speech, and the resolution of conflicts. Drawing on theories of pragmatics, semiotics, and intercultural communication, the article examines how paralinguistic signs can alter diplomatic messages and shape global political landscapes.